The study of symbiotic traits – nodulation and activity of nitrogen fixation – in different cultivars of spring vetch (Vicia sativa L.) - K. K. Sidorova; A. V. Goncharova (Вавиловский журнал генетики и селекции)
Common vetch Vicia sativa L. is one of the major annual fodder legume crops in Russia. Like other legumes, it can enter into symbiosis with nodule bacteria of the genus Rhizobium and to fix molecular nitrogen from the air. This ability contributes to the enrichment of soils with nitrogen and the possibility of growing crops on poor soils. Vetch symbiotic genes have not yet been identified, so the breeding of this crop is confined to the assessment of breeding material with regard to nodulation and very rarely to the activity of nitrogen fixation measured by the acetylene method. This paper presents the results of studies of nodulation and nitrogen-fixing activity that we conducted with four spring vetch cultivars raised at the Siberian Research Institute for Plant Industry and Breeding. Two varieties of forage pea, namely Druzhnaya and traditional cv. Falenskaya 42, were taken as references. The activity of nitrogen fixation was assessed from nitrogenase activity, assayed by the acetylene method. The study revealed significant varietal differences in nodulation and nitrogen fixation, determined on a gas chromatograph Tsvet 500, Russia. The nitrogenase activity rates in vetch cultivars under study varied from 2811 to 6890 С2Н4 nmol/ plant/h. Two of them, Lena and Priobskaya 25, were prominent in high nodulation nitrogen fixation rates. Nodulation in the two reference pea cultivars was weaker than in vetch. However, their nitrogen fixation activities were higher.